Performance of Single Base RTK GNSS Method versus Network RTK - Aykut, Nedim Onur; Gulal, Engin; Akpinar, Burak (UNIV NACIONAL DE COLOMBIA, 2015)
After the late 1990s, GNSS/GPS network RTK technology has become the preferred technique in the world, today widely used in various applications such as monitoring, early warning systems, and mapping and engineering applications. By the end of 2008, the CORS-TR network was being used for engineering applications to determine 3D positions across the whole of Turkey. On the other hand, single base RTK stations are being operated in Turkey. The YLDZ is one of these types of stations. It was established at the Yildiz Technical University by the Department of Geomatic Engineering in 2012. In this paper, the performance of the YLDZ station is examined by use of measurements in 5 Istanbul GPS Triangulation Network (IGNA) benchmark points, with five repeatability measurements up to 50 km from the station. The CORS-TR network RTK solution is used at the same points, and the results are compared. The measured coordinates produced by the two RTK solutions are compared with the IGNA point coordinates. Satellite geometry, initialisation time and the standard deviation of repeatability are also determined. The differences between measured and known coordinates are calculated as 1-2 cm horizontally and close to 3 cm vertically using the YLDZ single base RTK method.
Keywords: RTK GNSS; CORS; Single Base RTK; REFERENCE STATIONS; Geology